2008
DOI: 10.1037/1076-8998.13.2.95
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of task complexity on the relationship between regulatory foci and safety and production performance.

Abstract: Regulatory foci of promotion and prevention have been shown to relate differentially to occupational safety and production. This research proposes that task complexity can help explain the differences reported between these 2 self-regulatory processes and safety and productivity performance. Results revealed that promotion is positively related to production and prevention is positively related to safety regardless of task complexity. However, when task complexity is high, promotion negatively relates to safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
2
40
0
1
Order By: Relevance
“…As far as we are aware, this study was the first to examine specifically the relationship between promotion focus and performance predicting intention to leave in an organisational context. However, research examining similar relationships such as the relationship between feedback and performance when individuals have a strong promotion focus supports the findings in the current study (Idson and Higgins 2000;Van-Dijk and Kluger 2004;Wallace, Little and Shull 2008). Our findings add to this previous research, suggesting that the negative relationship between promotion focus and intention to leave may be stronger as performance increases particularly for higher performing employees.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As far as we are aware, this study was the first to examine specifically the relationship between promotion focus and performance predicting intention to leave in an organisational context. However, research examining similar relationships such as the relationship between feedback and performance when individuals have a strong promotion focus supports the findings in the current study (Idson and Higgins 2000;Van-Dijk and Kluger 2004;Wallace, Little and Shull 2008). Our findings add to this previous research, suggesting that the negative relationship between promotion focus and intention to leave may be stronger as performance increases particularly for higher performing employees.…”
Section: Discussionsupporting
confidence: 91%
“…Further research that explores the relationship between an individual's dominant regulatory focus and the extent to which he or she meets or exceeds performance targets over time may add to our knowledge of this area. This would extend previous research that found individuals with a promotion focus were more likely to excel with respect to the main goal of the activity, whereas individuals with a dominant prevention focus were more likely to outperform others in relation to the safety or compliance focus of the activity (Wallace et al 2008).…”
Section: Limitations and Future Researchsupporting
confidence: 52%
“…When there was a great deal of work to accomplish in a relatively small amount of time, individuals for whom efficiency was an obligation were willing to take shortcuts to meet these demands, even when doing so was risky. This finding provides some important context to prior research on the link between regulatory focus and safety, which has tended to find that a prevention focus was associated with greater safety and lower productivity (e.g., Wallace and Chen 2006;Wallace et al 2008). In those prior studies, regulatory focus was assessed as a general state possessed by individuals, akin to a domain-specific (i.e., workplace) personality trait.…”
Section: Discussionmentioning
confidence: 94%
“…Note: p \ .10; **p \ .01 rather than inducing an obligation-framed mindset ''in general'' (cf. Wallace and Chen 2006;Wallace et al 2008). Yet, a limitation of this design is that it is not possible to determine if the goal framing effects were driven by the ''efficiency is an obligation'' condition leading to increased utility under high risk and high workload conditions (as hypothesized), or if the results were driven by the ''safety is an obligation'' condition leading to decreased utility.…”
Section: Discussionmentioning
confidence: 97%
“…Prevention-focused people tend to follow rules and regulations conscientiously and to avoid errors (Higgins, 1997;Wallace et al, 2009), which suggests that they could make fewer picking errors. A promotion focus, on the other hand, has been linked to production performance (Wallace et al, 2009(Wallace et al, , 2008 and to sensitivity to the presence or absence of rewards (Kark and Van Dijk, 2007). However, these results are not generally applicable, and are subject to a very influential factor: the fit between people's regulatory focus and the goal that they have to pursue (Higgins, 2000).…”
Section: Regulatory Focusmentioning
confidence: 88%